2010
DOI: 10.1163/157075610x12610595764011
|View full text |Cite
|
Sign up to set email alerts
|

Breeding characteristics of the Lusitanian pine vole, Microtus lusitanicus

Abstract: Cover IllustrationPortions of mid-shaft cross-sections of the tibiae of juvenile animals (for details see Montes et al., this issue,. Instructions for AuthorsPlease visit Animal Biology web site at brill.nl/ab Animal Biology (online ISSN 1570-7563, print ISSN 1570 is published four times a year by: Brill,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…The distribution area of this species includes the south-eastern of France and most of the Iberian Peninsula. In northern populations reproduction takes place throughout the year, no resting period exists [46] as described also for the Lusitanian pine vole, Microtus lusitanicus [47], another Western European endemic sister species, which diverged from M. duodecimcostatus around 150 kyr ago [48]. In contrast, in the populations we studied here, which are at the meridional limit of their distribution area, Mediterranean pine voles may exhibit different breeding patterns at different geographically close locations.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution area of this species includes the south-eastern of France and most of the Iberian Peninsula. In northern populations reproduction takes place throughout the year, no resting period exists [46] as described also for the Lusitanian pine vole, Microtus lusitanicus [47], another Western European endemic sister species, which diverged from M. duodecimcostatus around 150 kyr ago [48]. In contrast, in the populations we studied here, which are at the meridional limit of their distribution area, Mediterranean pine voles may exhibit different breeding patterns at different geographically close locations.…”
Section: Discussionmentioning
confidence: 99%
“…This may partly explain why the abundance of pine voles is usually higher in agricultural areas (Vinhas 1993;Mira and Mathias 1994;Miñarro et al 2012). In fact, the permanent watering of soil, through dripping, is a common agronomic practice that facilitates the expansion of vole populations (Bertolino et al 2015), and in some cases it has been suggested to be a key factor explaining rodent outbreaks (Jareno et al 2015) and continuous reproduction throughout the year (Ventura et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Vole galleries remain open as a small hole in the ground [ 3 ] with superficial galleries used for feeding and escaping and deep ones used for storing food and nesting [ 1 ]. Microtus lusitanicus is a monogamous species: a couple of voles and their offspring (juvenile and sub-adult individuals) share the same gallery system [ 4 , 5 , 6 ]. Lusitanian pine voles are small sized rodents (body length: 77.5–105.0 mm; body mass; 14.0–19.0 g) with big head, blunt snout, small eyes and cylindrical body [ 1 ].…”
Section: Introductionmentioning
confidence: 99%